LARS&LISA: a universal school-based cognitive-behavioral program to prevent adolescent depression - Patrick Pössel; Eric Smith; Olivia Alexander (Psicologia: Reflexão e Crítica, 2018)
Abstract Adolescent depression is a prevailing international mental health concern as up to 27% of adolescents experience either subsyndromal depression or a major depressive episode by the age of 18. Depression in adolescence has been found to negatively impact current and future academic achievement, functioning, mental health, and quality of life. Accordingly, the authors emphasize the importance of proactively preventing depression (and its negative outcomes) instead of waiting and having to “fix” the problems after they have already developed. The current article begins with a discussion of the various types of prevention, including their respective advantages and disadvantages. Further and more importantly, the article’s primary focus is to provide a summary of the theoretical basis, development of, empirical support for, and content of a universal school-based cognitive-behavioral program to prevent adolescent depression entitled LARS&LISA (Lust An Realistischer Sicht & Leichtigkeit Im Sozialen Alltag). As the program exists within the overlapping realms of universal prevention, school-based programs, and cognitive-behavioral interventions, the content of this article is relevant to all three areas and offers insight into the development of depression prevention in general. Finally, empirical support for the positive effects of the program is presented and some ideas for further research are discussed.